2011
DOI: 10.1096/fj.11-185454
|View full text |Cite
|
Sign up to set email alerts
|

Origin‐specific epigenetic program correlates with vascular bed‐specific differences inRgs5expression

Abstract: Cells from multiple origins contribute to vascular smooth muscle cell (VSMC) development. Phenotypic heterogeneity of VSMCs is associated with their point of developmental origin; however, the mechanisms driving such differences are unknown. We here examined the mechanisms controlling vascular bed-specific differences in Rgs5 expression during development. Rgs5 levels were similar across different regions of the vasculature in neonatal animals but were >15-fold higher in descending aortas compared with carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…origins of vasculogenic cells (54,79). Indeed, vascular progenitor cells can arise from neural crest cells (32,41), splanchnic mesoderm (76), somitic mesoderm (74), and mesothelial cells (60).…”
Section: Discussionmentioning
confidence: 99%
“…origins of vasculogenic cells (54,79). Indeed, vascular progenitor cells can arise from neural crest cells (32,41), splanchnic mesoderm (76), somitic mesoderm (74), and mesothelial cells (60).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differences in VSMC characteristics such as gene expression have been attributed to their embryonic origin [25]. Also, studies suggest that when vessels prone to atherosclerosis are placed in a vascular region that does not typically develop atherosclerosis, they retain their predisposition to disease [26].…”
Section: Introductionmentioning
confidence: 99%
“…149 This difference led to a specific gene expression pattern in embrionic VSMCs, which converge in a unique phenotype in adult vessels, 150 although it has been proven that some genes can show peculiar expression patterns in different vascular beds. 151 Moreover, it was also reported that several cell types activate a subset of embronic genes in response to injury [152][153][154] ; this could provide new insights about the mechanism by which equal cells in different vessels (ie, aorta, carotid) respond in disparate ways to similar stimuli.…”
Section: Potential Limitations and Caveats Of The Therapeutic Use Of mentioning
confidence: 97%